2007
DOI: 10.1007/s10350-007-9041-2
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Eradication of Intra-Anal Warts with Argon Plasma Coagulator Combined with Imiquimod Cream Compared with Argon Plasma Coagulator Alone: A Prospective, Randomized Trial

Abstract: Combination therapy with argon plasma coagulator plus imiquimod cream results in earlier clearance of intra-anal warts in both immunocompetent and immunocompromised patients; however, it does not affect the rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
0
28
0
3
Order By: Relevance
“…In a small RCT10 of combined treatment of intra-anal warts with argon plasma coagulation and imiquimod 5% cream versus argon plasma coagulation alone, no statistically significant differences were seen for short-term CC and long-term recurrence (GRADE: moderate). None of the participants experienced pain or dropped out due to AE.…”
Section: Resultsmentioning
confidence: 98%
“…In a small RCT10 of combined treatment of intra-anal warts with argon plasma coagulation and imiquimod 5% cream versus argon plasma coagulation alone, no statistically significant differences were seen for short-term CC and long-term recurrence (GRADE: moderate). None of the participants experienced pain or dropped out due to AE.…”
Section: Resultsmentioning
confidence: 98%
“…Here, although shown to be effective and safe, the procedure was marked by recurrence rates of up to 33 % . A study that compared APC with a combination of APC and imiquimod confirmed the safety and efficacy of APC in the subgroup of HIV‐positive individuals . According to the authors´ opinion, only monofocal AIN or AIN‐lesions located in two quadrants of the anal circumference should be surgically removed, as widespread excision might induce stenosis or strictures.…”
Section: Treatment Of Anal Intraepithelial Neoplasiamentioning
confidence: 96%
“…Das Verfahren konnte als effektiv und sicher charakterisiert werden, Rezidive traten aber in bis zu 33 % auf . Eine Studie, die die APC mit einer Kombinationsbehandlung aus APC und Imiquimod verglich, legte in einer Subgruppe Daten zu HIV‐Infizierten vor, die das zu Sicherheit und Effektivität Gesagte bestätigte . Nach Meinung der Autoren sollten nur monofokale bzw.…”
Section: Therapie Der Analen Intraepithelialen Neoplasieunclassified